2016
DOI: 10.1016/j.devcel.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

PIKfyve Regulates Vacuole Maturation and Nutrient Recovery following Engulfment

Abstract: Summary The scavenging of extracellular macromolecules by engulfment can sustain cell growth in a nutrient-depleted environment. Engulfed macromolecules are contained within vacuoles that are targeted for lysosome fusion to initiate degradation and nutrient export. We have shown that vacuoles containing engulfed material undergo mTORC1-dependent fission that redistributes degraded cargo back into the endosomal network. Here we identify the lipid kinase PIKfyve as a regulator of an alternative pathway that dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(154 citation statements)
references
References 46 publications
12
141
1
Order By: Relevance
“…However, S6K remained phosphorylated in apilimod-treated cells, suggesting that mTORC1 was active. These observations are consistent with Wang et al and Krishna et al who also showed that mTORC1 retains its activity in PIKfyve-abrogated cells (Wang et al, 2015;Krishna et al, 2016). We considered the possibility that mTORC1 and starvation controls PIKfyve activity instead, which may then modulate TFEB, perhaps by a PtdIns(3,5)P 2 -dependent localization of TFEB to lysosomes, as has been shown for Tup1, a transcription factor in yeast that controls galactose metabolism (Han and Emr, 2011).…”
Section: Pikfyve and Tfeb Regulationsupporting
confidence: 89%
See 2 more Smart Citations
“…However, S6K remained phosphorylated in apilimod-treated cells, suggesting that mTORC1 was active. These observations are consistent with Wang et al and Krishna et al who also showed that mTORC1 retains its activity in PIKfyve-abrogated cells (Wang et al, 2015;Krishna et al, 2016). We considered the possibility that mTORC1 and starvation controls PIKfyve activity instead, which may then modulate TFEB, perhaps by a PtdIns(3,5)P 2 -dependent localization of TFEB to lysosomes, as has been shown for Tup1, a transcription factor in yeast that controls galactose metabolism (Han and Emr, 2011).…”
Section: Pikfyve and Tfeb Regulationsupporting
confidence: 89%
“…We do not understand how PIKfyve modulates lysosome fission dynamics. However, we speculate that mechanisms that offset lysosome coalescence are distinct from those that drive vesiculation and recycling (Krishna et al, 2016;Bryant et al, 1998;Rutherford et al, 2006). One interesting possibility may relate to contact sites between endo/lysosome and the endoplasmic reticulum since these have been shown to demarcate and assemble molecular machines that catalyse endolysosome fission (Friedman et al, 2013;Rowland et al, 2014).…”
Section: Cc-by-nc-ndmentioning
confidence: 95%
See 1 more Smart Citation
“…Because of this specialized function, lysosomes receive cargo via multiple pathways, including macroautophagy (autophagy hereafter) and macropinocytosis, which allows for scavenging of intracellular and extracellular nutrients, respectively (1). Autophagy and macropinocytosis are both regulated by the mammalian target of rapamycin complex 1 (mTORC1) (2). In turn, the lysosome membrane directly regulates mTORC1 by housing key mTOR regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Macropinocytosis has been shown to act similarly to allow cancer cells to scavenge extracellular proteins [5]. Entosis instead supplies bulk nutrients in the form of whole cells, where, on average, winner cells ingest two losers, providing a large nutrient supply that is well suited to support the outgrowth of selected cells in the population.…”
mentioning
confidence: 99%